Analysis of Influencing Factors on The Provision of Birth Control Equipment and Materials at The Lahomi Non-Inpatient Health Center Unit, West Nias Regency - Sri Lestari Nasution; Dermawati Laia; Ermi Girsang (Biology, Medicine, & Natural Product Chemistry, 2025)
The quality and access to family planning services demands a paradigm shift, especially among service providers, which in this case are Bapermas and KB. That is why service must be carried out on the basis of volunteerism, openness, and honesty. One of the service providers that is still questionable about the quality of its services is the Community Empowerment, Women and Family Planning Agency.  The implementation of the provision of kb tools and materials has not been carried out properly and correctly. The purpose of this study was to analyze the factors of influence on the provision of birth control equipment and materials at the UPT Non-Inpatient Health Center Lahomi, West Nias Regency. The type of research used was quantitative analytics. Dessay research is a cross-sectional study. The sampling technique in this study was the total population, namely the entire population was used as a research sample, then the number of samples in the study was 170 employees. The results of the study explained that there was an influence between supervision, direction, control, supervision and budgeting on the provider of birth control equipment and materials in Lahomi Health Center, Nias Regency. West. It is hoped that with this research, Lahomi Health Center will improve the quality of services, especially in the provision of birth control tools and materials.